Role of Extracellular Vesicles in Chronic Post-Embolic Pulmonary Hypertension: Data from an Experimental Animal Model and Patients - Elva Mendoza-Zambrano; Verónica Sánchez-López; Belén Gómez-Rodríguez; Inés García-Lunar; Daniel Pereda-Arnau; Luis Jara-Palomares; Teresa Elías-Hernández; Ana García-Álvarez; Remedios Otero-Candelera (Biomedicines, 2025)
Background: The pathogenesis of chronic thromboembolic pulmonary hypertension (CTEPH) involves a multifaceted interplay of factors, including incomplete thrombus resolution, endothelial dysfunction, and vascular remodeling. Recent studies have highlighted the role of extracellular vesicles (EVs) in vascular diseases, suggesting their potential involvement in CTEPH progression. This study aims to investigate the role of EVs from various cellular sources in the development of CTEPH. Methods: An experimental study was conducted using 11 male three-month-old Large-White pigs. The EVs of endothelial origin (EEVs; CD146+), leukocyte-derived EVs (LEVs; CD45+, CD44+), and consistent with mesenchymal-origin EVs (CD90+, CD105+) were quantified. Measurements were taken at baseline, after the first embolization, and prior to each subsequent weekly embolization. Embolizations were repeated until chronic pulmonary hypertension (PH) was generated. Based on these findings, a clinical case-control study was performed involving nine patients previously diagnosed with CTEPH and 18 patients with pulmonary embolism who did not develop CTEPH after two years of follow-up. Results: The experimental study, consistent with the mesenchymal-origin EVs, exhibited a progressive decrease below baseline levels; LEVs decreased after PH was established, while EEVs remained elevated throughout the study. Subsequently, in the clinical case-control study, CD45+ LEVs emerged as a significant association of CTEPH, with an odds ratio (OR) of 21.25 (95% CI: 1.91–236.00; p = 0.013). Conclusions: Inflammation involving LEVs and EEVs plays a crucial role in sustaining the vascular alterations leading to pulmonary vasculature remodeling in CTEPH.